DILEMA FEMINIS SEBAGAI REAKSI MASKULIN DALAM TRADISI PERNIKAHAN BUGIS MAKASSAR - Syahrul Syahrul (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2017)
This paper seeks to expose feminist existence in the tradition of Bugis Makassar marriage by revisiting the position of Siri 'culture as the emancipation of human values, especially with regard to feminist and masculine essence in marriage. The marriage system shows the unclear direction or unrelatedness between the Siri 'values tradition and the concrete reality of feminist existence. The marriage system of Bugis Makassar is characterized by a shift in tradition which then raises the value of materialism into Siri 'culture. The problem becomes more complicated when faced with “uang panaik” tradition that so neutralize myths as a measure of establishment and masculine responsibility, so that the masculine reaction to the tradition of marriage Bugis Makassar feels necessary. Because this is what will create the feminist dilemma in the tradition of marriage.